Unusual Histopathological Findings in Mechanically Removed Stroke Thrombi – A Multicenter Experience - Aspegren, Oskar; Staessens, Senna; Vandelanotte, Sarah; Desender, Linda; Cordonnier, Charlotte; Puy, Laurent; Bricout, Nicolas; De Meyer, Simon F.; Andersson, Tommy; Arnberg, Fabian (Frontiers in Neurology, 2022)
Background: Several studies have investigated the histopathology of mechanically retrieved thrombi from stroke patients. Thrombi with unusual components constitute about 1-2% of all stroke thrombi in clinical practice. Knowledge about these rare components is limited. Objectives: To characterize the histopathology of unusual stroke thrombi from a real-world setting with relation to clinical presentation, patient characteristics and procedural aspects of mechanical thrombectomy. Methods: One-thousand and eight thrombi retrieved from stroke patients with mechanical thrombectomy at three different hospitals were retrospectively reviewed for unusual histological components. Fifteen thrombi were included in the study for further histopathological analysis. Clinical data and data on procedural aspects were collected. Results: We identified six cases with large amounts of extracellular DNA, of which three were calcified. All six cases except one received anticoagulant therapy. We describe two types of calcifications that differ with respect to general calcification morphology, von Kossa staining pattern, macrophage immunophenotype and presence of multinucleated giant cells. Cholesterol-rich (n=3), adipocyte-like pattern-rich (n=2), collagen-rich (n=2) and myxomatous (n=1) thrombi were also identified and are discussed with regard to pathogenesis and clinical and intervention characteristics. Finally, a thrombus with parts of a vascular wall is described. Suggestions for future studies are made and clinical and technical aspects of the management for these rare but important patients are discussed. Conclusion: In our retrospective multicenter study, we characterized stroke thrombi histopathologically and found subgroups of thrombi defined by presence of rarely seen components. These defined subgroups showed relation to underlying cardiovascular disease, patient characteristics, and mechanical thrombectomy technique. Knowledge about these components may increase our understanding of stroke pathophysiology and influence interventional procedures.